Incorporating climate change in conservation planning for freshwater fishes. Issue 8 (17th April 2014) - Bond, Nick R.; Thomson, James R.; Reich, Paul; MacIsaac, Hugh
Abstract Aim To assess how the inclusion of predicted climate‐change‐related range shifts alters the spatial prioritization of habitats and predicted biodiversity benefits from systematic conservation planning under alternative realized climates. Location Victoria, Australia. Methods We combined predicted distribution patterns of freshwater fish under multiple climate scenarios with marginal benefit conservation planning algorithms to compare conservation outcomes from multiple planning scenarios based on predicted present and future range‐shifted distributions. For each of these planning options, we examined the outcomes under a range of possible realized climates. Results Expected conservation outcomes under future climate scenarios were always better when potential range shifts were incorporated into the planning process, irrespective of which climate scenario was realized. However, the differences in conservation outcomes between planning strategies were often small, and expected conservation outcomes always were worse under altered climate scenarios than under a stable baseline climate scenario. River segments with variable rankings across planning scenarios reflected areas where risks of maladaptive prioritization are potentially high. Main conclusions This study highlights that greatest conservation gains will come from ongoing efforts to limit the degree of global warming. Nevertheless, within the constraints imposed by a changing climate, the inclusion of future range shifts in conservation plans can help insure against ineffective and potentially maladaptive prioritization decisions. The acknowledged caveats around statistical predictions of species distributions and range shifts also need to be considered when acting on the outputs from modelled predictions such as these.